Inovasi Pelayanan Publik (Studi pada Pelayanan Kesehatan Melalui Program Gebrakan Suami Siaga di Puskesmas Gucialit Kabupaten Lumajang) - Ariyani, Arik; Indah Mindarti, Lely; Nuh, Mohammad (Jurnal Ilmiah Administrasi Publik, 2016)
Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) in Indonesia is still high. The central government and the local governments charged jointly conduct various innovative efforts of health. As an example of Puskesmas Gucialit Lumajang in addressing the issue of high maternal and infant mortality in the region through Program breakthrough husband standby. The results showed that the standby husband breakthrough innovation has been implemented properly. Many services provided, quality of service is better, and showed the declining trend in maternal and infant mortality in the region Gucialit. Program breakthrough husband standby innovation success capable of being expanded into a container that is wider in 2013 through a program dear mother and child.